G394(P) Learning from picu transfers from a paediatric emergency department and paediatric ward. (12th March 2018) - Cuevas-Asturias, S; Grossman, S; Maggs, T; Runnacles, J; Sinitsky, L
Abstract : Aims: Local hospital Paediatricians often rely on updates from retrieval services for information about their patients transferred to Paediatric intensive care units (PICU). This quality improvement project aimed to increase local hospital knowledge about their PICU transfers and identify areas for improvement to enhance patient safety and clinical care. Methods: In November 2016 a new incident log was implemented to collect data on PICU transfers from the Emergency Department and Paediatric ward of one district general hospital. Between January and September 2017, a multi-disciplinary team met monthly to review the Electronic Document and Records Management (EDRM) system of all patients transferred to PICU in the previous month(s). The multidisciplinary team included medical and nursing representation from Paediatric, Emergency and Anaesthetic departments and the outreach resuscitation team. EDRM was reviewed using an adapted RECALL (Rapid Evaluation Cardiorespiratory Arrest with Lessons for Learning) tool. The RECALL tool provided a structured template for retrospective case note review of patient management, including monitoring, escalation and medical reviews, in addition to staffing issues, debriefs and parental feedback. Areas for improvement were shared across services by monthly newsletters and updates at teaching sessions and departmental risk meetings. Results: Between November 2016 and September 2017, 26 children aged 2 days to 15 years were transferred to PICU, of which 69% were from the Emergency Department. The primary problem was respiratory failure in 50% of cases. In the first 6 months many cases had incomplete Paediatric Early Warning Score (PEWS) monitoring and/or poor escalation of care documentation. Shared learning and teaching on PEWS resulted in recent cases of exemplary practice. Initially EDRM was incomplete for patients moved to theatre from the emergency department for intubation. Recommendation to scan notes prior to moving resulted in complete EDRM records in all subsequent reviews. The multidisciplinary team recognised that parental views remained unheard and so initiated parents being offered the Friends and Family feedback card post-PICU repatriation. Conclusion: Shared learning from regular structured multidisciplinary case note reviews of PICU transfers results in improvements in the management, safety and documentation of children presenting with critical illness.